Pelatihan dan Pendampingan Jaringan Komputer dengan Mikrotik di Pondok Pesantren Modern Terpadu Dr. Muhammad Natsir Alahan Panjang Kabupaten Solok - Heru Dibyo Laksono; Reri Afrianita; Mumuh Muharram; Novizon Novizon (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Training of Computer network using Miktrotik at the Integrated Modern Islamic Boarding School of Dr. Muhammad Natsir at Alahan Panjang is one of the solutions to overcome the problem of the effectiveness and efficiency computer user. The training was started by a field survey to laboratory of the information and communication technology (ICT) at the School. In this survey, discussions were held on what problems are very important and get priority to find solutions in increasing the effectiveness and efficiency of computer use at the School. The results of the survey agreed that computer network training with Mikrotik would be held in order to increase the effectiveness and efficiency of computer use on it. The second activity was the preparation of computer network training with Mikrotik. Preparation was carried out in the form of discussions with teammates to determine materials and methods that were more efficient and effective in the implementation of computer network training with Mikrotik at the Information and Communication Technology (ICT) laboratory. The results of the discussion agreed that the training would be provided in the form of presentations and hands-on practice. The third activity was the implementation of computer network training with mikrotik. This training was provided for 2 days, namely Saturday and Sunday. The first day was done by shared knowledge about the basics of computer networks and Mikrotik. The second day, students did a computer network training with Mikrotik. The fourth activity was the evaluation of computer network training activities with Mikrotik, to evaluate the activities that have been carried out and to obtain suggestions and input for future improvements.